Evaluation of Plasma Cystatin C Depending on ‎Physiological Factors in Healthy Iraqi People - Al-Ziaydi, Ahmed Ghdhban (Medical Science Journal for Advance Research, 2024)
Background: Cystatin C is a small protein formed by nucleated cells and has gained significant attention as a potential test for various health conditions, including cardiovascular diseases and impaired kidney functions. Although existing research on cystatin C levels in different populations, there remains a gap in understanding its variations in healthy Iraqi individuals, particularly concerning gender, age, and body mass index (BMI). Aim: This study addresses this gap by evaluating the evolution of plasma cystatin C levels in 180 healthy Iraqi volunteers. Methods: the samples were categorized based on age, gender, and obesity status. Results: showed no significant difference (p-value ≤ 0.05) according to gender with the mean value of Cystatin C as 0.8511 pg/ml and 0.7881 pg/ml in male and female groups, respectively. The result showed gradually elevated levels in Cystatin C according to age, when Cystatin C values were 0.6676 ± 0.1918 pg/ml, 0.8339 ± 0.3416 pg/ml, 0.8442 ± 0.3422 pg/ml, 0.8930 ± 0.3471 pg/ml, 1.103 ± 0.3356 pg/ml in 40s, 50s, 60s, 70s, and 80s groups, respectively (p-value ≤ 0.05). Also, the result showed significant differences (p-value ≤ 0.05) in Cystatin C levels according to BMI with mean values of 0.7578 ± 0.1036 pg/ml, 0.7999 ± 0.3176 pg/ml, 0.9218 ± 0.2629 pg/ml, 1.0280 ± 0.4693 pg/ml in normal BMI, overweight, obese, and extremely obese, respectively. Conclusion: the study concludes that age and BMI significantly influence serum cystatin C levels in healthy people. These findings provide valuable insights into the physiological factors affecting cystatin C levels in the Iraqi population and underscore the need for finding reference values tailored to this specific demographic.